Epistemic Transformation: Implications and Implementation of Islamic Character Education in the Era of Artificial Intelligence - Ahmad Fauzi Zakaria; Nurhasan Nurhasan; Yanti Amali Afifah; Aan Hasanah; Bambang Samsul Arifin (PT. Pusmedia Group Indonesia, 2026)
The rapid development of Artificial Intelligence (AI) has created new challenges and opportunities for character education within Islamic educational institutions. This study aims to analyze the implications and implementation of character education in Islamic education in the AI era and to formulate a conceptual model that integrates theological values with technological advancement. This research employed a qualitative approach using library research methods. Data were collected from reputable international and national journal articles indexed in Scopus and accredited databases published between 2021 and 2026. Data analysis was conducted through comparative and critical content analysis. The findings reveal four major themes. First, character education in Islamic education has undergone a conceptual transformation from universal character values toward transcendental akhlaq rooted in tawhid, faith, and spiritual consciousness. Second, its implementation faces significant challenges, particularly excessive administrative burdens that weaken teachers' role-modeling function (uswah hasanah). Third, the emergence of AI encourages the development of an